Verbal abuse and internalizing problems in early adolescence: negative attributional style as mediator - Tan, Irene Li Yin; Mansor, Mariani; Abdullah, Rohani (Universiti Putra Malaysia Press, 2013)
This study examined the contributions of verbal abuse to internalizing problems among 324 early adolescent students (aged 11-13 years) in Selangor, and the mediating role negative attributional style plays in this relationship. Students were selected using a cluster sampling method and responded to a self-administered questionnaire. Children.s Perception of Parental Verbal Aggression (CPPVA; Solomon & Serres, 1999), The Children.s Attributional Style Questionnaire (CASQ; Seligman et al., 1984) and Internalizing Symptoms Scale for Children (ISSC; Merrell & Walters, 1998) were used to measure the variables in this study. Data were analyzed using Baron and Kenny.s (1986) statistical framework for assessing the mediational effects. Findings suggest that negative attributional style partially mediates verbal abuse and internalizing problems. This study sheds light on how verbal abuse contributes to internalizing problems in Asian context. Implications for intervention and prevention work related to internalizing problems among early adolescent students are also discussed.